2018
DOI: 10.3389/fmicb.2018.02903
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality and Total Microbial Load: A Double-Threshold Identification Procedure Intended for Space Applications

Abstract: During longer-lasting future space missions, water renewal by ground-loaded supplies will become increasingly expensive and unmanageable for months. Space exploration by self-sufficient spacecrafts is thus demanding the development of culture-independent microbiological methods for in-flight water monitoring to counteract possible contamination risks. In this study, we aimed at evaluating total microbial load data assessed by selected early-warning techniques with current or promising perspectives for space ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Conversely, we found that AMR‐cap enrichment has the opposite effect on samples obtained from wastewater treatment plants. Wastewater samples are notorious for having a high microbial load and, in comparison, to other sample types have higher levels of ARGs (Amalfitano et al ., 2018). The poultry litter samples represent a middle ground between the built environment and wastewater samples, as some samples and resistance genes are sequenced at deeper levels with AMR‐cap enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, we found that AMR‐cap enrichment has the opposite effect on samples obtained from wastewater treatment plants. Wastewater samples are notorious for having a high microbial load and, in comparison, to other sample types have higher levels of ARGs (Amalfitano et al ., 2018). The poultry litter samples represent a middle ground between the built environment and wastewater samples, as some samples and resistance genes are sequenced at deeper levels with AMR‐cap enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that pathogenic microorganism having the smallest size in water be determined before selection of a proper membrane for cold pasteurization or sterilization of water. Countermeasures for contaminations by "unexpected" pathogens may also be important for avoiding health risks in consumers (Amalfitano et al, 2018 ). This aspect has also be highlighted by other studies (Orhan et al, 2021 ; Beck et al, 2021 ).…”
Section: Scientific Basis Of Membrane Filtration To Remove Microorgan...mentioning
confidence: 99%
“…Some drawbacks of the method are partly circumvented by using external and internal standards and by operating under controlled reproducible settings. Therefore, the correlation between intracellular ATP content and microbial cell counts will rely on a robust cross-calibration with results from other reference methods (Amalfitano et al, 2018b;Hammes et al, 2010). It has been calculated that the average ATP-per-cell content is approximately 1.75 x 10 -10 nmol/cell or 6.87 x 10 -17 g ATP/cell (K. .…”
Section: Sequencing-based "-Omics" Approaches For Microbial Communitymentioning
confidence: 99%
“…The mature technologies, herein entitled for water microbial monitoring in space, showed their own critical advantages and limitations (table 1). Both current and future applications in space will be necessarily bounded by the definition of novel standards of microbial quality (i.e., other than those applied on Earth by cultivation-dependent approaches) (Amalfitano et al, 2018b), but also by a compromise between the best analytical performances and detrimental technical issues to cope with during spaceflights.…”
Section: Comparative Analysis Of Space-relevant Technological Featuresmentioning
confidence: 99%
See 1 more Smart Citation